Biosynthetic Studies of the Notoamides: Isotopic Synthesis of Stephacidin A and Incorporation into Notoamide B and Sclerotiamide - Finefield, Jennifer M. (2011)
[Image: see text] The advanced natural product stephacidin A is proposed as a biosynthetic precursor to notoamide B in various Aspergillus species. Doubly (13)C-labeled racemic stephacidin A was synthesized and fed to cultures of the terrestrial-derived fungus, Aspergillus versicolor NRRL 35600, and the marine-derived fungus, Aspergillus sp. MF297-2. Analysis of the metabolites revealed enantiospecific incorporation of intact (–)-stephacidin A into (+)-notoamide B in Aspergillus versicolor, and (+)-stephacidin A into (–)-notoamide B in Aspergillus sp. MF297-2. (13)C-Labeled sclerotiamide was also isolated from both fungal cultures.